Impact of Sacubitril/Valsartan on Clinical and Echocardiographic Parameters in Heart Failure Patients With Reduced Ejection Fraction: Data From a Real Life 2-year Follow-Up Study - Armentaro, Giuseppe; D’Arrigo, Graziella; Magurno, Marcello; Toscani, Alfredo F.; Condoleo, Valentino; Miceli, Sofia; Cassano, Velia; Maio, Raffaele; Arturi, Franco; Tripepi, Giovanni; Sesti, Giorgio; Sciacqua, Angela (Frontiers in Pharmacology, 2021)
Heart failure (HF) represents a widespread health problem characterized by high morbidity and mortality. Sacubitril/Valsartan (sac/val) has improved clinical prognosis in patients affected by HF with reduced ejection fraction (HFrEF). The aim of this study was to evaluate the effectiveness and durability of sac/val treatment on the clinical, hemodynamic and echocardiographic parameters, in real-life consecutive HFrEF outpatients, evaluated up to two-years of follow-up. We collected 300 repeated observations over time in 60 patients suffering of HFrEF and symptomatic despite optimal drug therapy. Patients with left ventricular ejection fraction (LVEF) <35 and II-III NYHA functional class were considered. All patients underwent to clinical-instrumental and laboratory determinations and Minnesota Living with HF Questionnaire (MLHFQ) every 6 months until 24 months to evaluate possible clinical benefits and adverse events. During a two-year follow-up period and through a 6-monthly control of the study variables both clinical, hemodynamic, biochemical and echocardiographic parameters significantly improved, in particular cardiac index (CI), both atrial and ventricular volumes and global longitudinal strain (GLS). Furthermore, there was a reduction of NT-proBNP levels and betterment of renal function and NYHA functional class, demonstrating the efficacy and durability of sac/val treatment. In a multiple linear mixed model the longitudinal evolutions of CI were associated to concomitant changes of GLS and E/e’ ratio. Our study, contemplating the collection of 300 repeated observations in 60 patients, provides a complete and detailed demonstration of sac/val effects, showing effectiveness, safety and effect durability of the treatment every six months up to two-years of follow-up with significant improvement of several clinical, hemodynamic and echocardiographic parameters in HFrEF outpatients.